The Common Ground Between Japanese and Korean Buddhism in the Early Modern Period: Changes in the Perception of the Mechanism of the State–Buddhist Relationship - Yong Tae Kim (Religions)
The East Asian world has shared both universal characteristics and regional particularities, forming a Buddhist cultural area for more than 1500 years. One of the main features of East Asian Buddhism is a “state–Buddhist link”. This article will focus on the early modern period, and on the periphery, Korea and Japan, rather than the center, China. If we can identify the attributes of the institutional connection between the state and Buddhism in this peripheral area of the East Asian world, and in a period when Buddhism was less prominent than before, we can understand it as a long-term universal characteristic of East Asian Buddhist cultures. In this article, I have tried to locate the common ground between Japanese and Korean Buddhism in the early modern period at two points: the change in the perception of Buddhism in the early modern period and the mechanism of the relationship between the state and Buddhism. The common ground here is that there is a movement in the two countries to break away from the negative perception of Buddhism in the early modern period and approach its historical reality. In terms of the mechanism of the relationship between the state and Buddhism, the Edo period saw the implementation of the temple parish system, which linked temples and people in each region, allowing the shogunate to indirectly control the people, while each sect was able to establish financial stability and thus its sectarian identity. In late Chosŏn, the institutionalization of the monk state service allowed the state to utilize the monk labor force and the surplus goods of the temples, and in return, the Buddhist community was allowed to rather peacefully exist in Confucian society. This shows that there was a close relationship between the two. There are many differences between Japanese and Korean Buddhism in the early modern period, but they share the characteristics of state Buddhism, where the state and Buddhism were institutionally related. The mechanism of the win–win relationship between the state and Buddhism can be understood as a universal characteristic of East Asian Buddhist history beyond Japan and Korea in the early modern period.